EVALUASI KEBIJAKAN KELOMPOK KERJA OPERASIONAL POSYANDU DI KABUPATEN SIGI - Musa, Agus Robinson (Katalogis, 2019)
The success of the Posyandu Operational Working Group (Pokjanal) in Sigi district from 2011 to 2018, can be said that it has not materialized as expected from the policy of the Minister of Home Affairs of the Republic of Indonesia Number.411.3 / 6124 / PMD concerning Implementation of Posyandu Pokjanal Formation in Regions. This study aims to find out why the Posyandu Operational Working Group (Pokjanal) failed in carrying out its duties and also to know the failure of the Posyandu Operational Working Group (Pokjanal) using theoretical analysis of the Public Policy Evaluation of William N. Dunn's Evaluation Model namely Effectiveness, Efficiency, Adequacy, Alignment, Responsiveness and Accuracy. The research method used is a qualitative research where researchers conduct interviews with a number of informants who are qualified in the field of implementation of the Posyandu Operational Working Group (Pokjanal). Indeed, the success of the Posyandu Operational Working Group (Pokjanal) lies in the high commitment of all cross-program and related sectors, because each region during the implementation period certainly has its own problems. And with the William N Duun model evaluation theory approach which emphasizes on 6 (six) evaluation criteria, namely; 1) Effectiveness, 2) Efficiency, 3) adequacy, 4) Alignment, 5) Resposivity, and 6) Accuracy. The results of the study indicate that the implementation of the Posyandu Operational Working Group (Pokjanal) has not been achieved because based on William N Duun's evaluation theory approach of the 6 criteria has not been fulfilled. And the conclusion of this study is the implementation the Indonesia Minister of Internal Affairs Republic of Indonesia after 7 (seven) years is not reached.